Violation of Notary Code of Ethics in Using Social Media for Self-Promotion Through Video Blog Form - IRIANTORO, Agung; YUNIDA, Arlia (Protection: Journal Of Land And Environmental Law, 2024)
Legal consequences for Notaries who violate the rules contained in the Notary Code of Ethics: The Notary Honorary Council can impose code of ethics sanctions on Notaries who violate the code of ethics, in this case, related to publication and self-promotion on social media in the form of vlogs, by the problems discussed in this legal research. The code of ethics sanctions for Notaries who violate the rules related to publication or self-promotion on social media (electronic) based on Article 6 paragraph (1) of the Notary Code of Ethics is in the form of reprimands, warnings, temporary suspension from membership of the Association, honorable suspension from membership of the Association, or dishonorable suspension from membership of the Association. In the context of the case of violation of the code of ethics by Notary PRS related to the circulation of the vlog, the sanctions given to Notary PRS are in the form of sanctions of the code of ethics or accountability according to the code of ethics and his position based on the results of the examination of Notary PRS in the Minutes of Examination issued by the Malang Regional Honorary Council which states that Notary PRS promises to delete the video that has been circulated and will not commit the act again